Herpes Encephalitis Masquerading as Tumor. (30th March 2011) - Peeraully, Tasneem; Landolfi, Joseph C.
Abstract : A 54 year old lady presented with lethargy and 15 kg weight loss over the past year. CT scan of the head revealed left temporal lobe hypodensity with a discrete area of hemorrhage within the left mesial temporal lobe. Due to concerns about impending central herniation, lumbar puncture was not performed. MRI of the brain showed a large lesion of the left temporal lobe, extending to the left frontal lobe, and very patchy meningeal enhancement. There was a noncontiguous lesion of the right insula. A differential diagnosis of herpes simplex encephalitis (HSE) and multifocal infiltrative glioma was entertained. MR spectroscopy demonstrated an increased choline peak at the level of the medial left temporal lobe and MR perfusion demonstrated patchy areas of hyperperfusion within the left anterior temporal lobe, both suggestive of neoplastic disease. Following open brain biopsy, pathology revealed herpes simplex virus (HSV) positive nuclei in the cortex and subcortical white matter. As both herpes simplex encephalitis and low-grade glioma demontrate MRI findings of hypointensity on T1 images and hyperintensity on T2 images, the diagnosis of herpes encephalitis can be clouded by confounding factors, especially when cerebrospinal fluid (CSF) cannot be obtained.